PELATIHAN DIGITAL MARKETING UNTUK PENGUATAN KAPASITAS BUMDES KECAMATAN KUPANG BARAT - Alfry Aristo Jansen Sinlae; Paskalis A. Nani; Maria Augustin Lopes Amaral; Adrianus Ketmoen; Gerardus Diri Tukan; Paulus Adrianus K. L. Ratumakin (LPPM Universitas Bina Bangsa, 2023)
This Community Service activity was carried out by lecturer team of Widya Mandira Catholic University at the Digital Marketing Training for BUMDes in West Kupang District with two villages namely Kuanheun Village and Bolok Village. This training aims to provide knowledge about digital marketing so that it can be used to promote BUMDes business units in Kuanheun Village and Bolok Village, which will be held on July 26, 2022. The methodology used is a modern approach with a participatory rural approach in the form of training and mentoring which is generally done through three stages; preparation, training and evaluation, to make it easier for trainees to understand in Kuanheun Village and Bolok Village. The participants of this training are representatives of several people with a total of 35 people including lecturers, students, Village Government, Village Management Board, BUMDes management, UMKM actors, community leaders, and youth groups. The results obtained are can increase knowledge for participants in Kuanheun Village and Bolok Village that the importance of Digital Marketing is to increase sales and for the sustainability of the business being run. This activity is expected to help BUMDes actors in increasing their income and also increasing knowledge in the digital era so that they are not eroded by changing times